A survey of the small RNA population during far-red light-induced apical hook opening - Li, Ying; Varala, Kranthi; Hudson, Matthew E. (Frontiers in Plant Science, 2014)
Photomorphogenesis is a mechanism employed by plants to regulate their architecture and developmental program in response to light conditions. As they emerge into light for the first time, dark-grown seedlings employ a rapid and finely-controlled photomorphogenic signaling network. Small RNAs have increasingly been revealed to play an important role in regulating multiple aspects of plant development, by modulating the stability of mRNAs. The rapid alteration of the mRNA transcriptome is a known hallmark of the de-etiolation response, thus we investigated the small RNA transcriptome during this process in specific seedling tissues. Here we describe a survey of the small RNA expression profile in four tissues of etiolated soybean seedlings, the cotyledons, hypocotyl and the convex and concave sides of the apical hook. We also investigate how this profile responds to a 1-h far-red light treatment. Our data suggests that miRNAs show a different global profile between these tissues and treatments, suggesting a possible role for tissue- and treatment-specific expression in the differential morphology of the seedling on de-etiolation. Further evidence for the role of miRNA in light-regulated development is given by the de-etiolation responses of a hypomorphic ago1 mutant, which displays reduced and delayed photomorphogenic responses in apical hook and cotyledon angle to far-red light.